1997
DOI: 10.1021/es960574x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Cr(III) and Cr(VI) to Marine Mussels from Solute and Particulate Pathways

Abstract: Mussels have been extensively used as biological monitors of coastal contamination. This study measured the assimilation efficiencies (AEs) of Cr(III) and Cr(VI) in the mussel Mytilus edulis from ingested food, uptake from the dissolved phase, and the physiological efflux rates following uptake. A bioenergetic-based kinetic model was then employed to determine the relative contributions of different Cr species and their accumulation pathways to the overall concentration of Cr in mussels. The concentration fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 47 publications
13
92
2
Order By: Relevance
“…The Hg accumulation in marine fish primarily depends on some important biokinetic parameters: assimilation from the ingested prey, uptake constants from the aqueous phase, de-toxification rate (Wang, 2012;Wang et al, 1997Wang et al, , 1998Wang and Fisher, 1999;Dang and Wang, 2011) and environmental features (e.g., Hg concentration and speciation in seawater, dietary sources, etc.) (Wang and Wong, 2003 Several studies have demonstrated that Hg concentrations in the muscles of marine organisms proportionally increase with size and age (Lange et al, 1994;Burger et al, 2001;Green and Knutzen, 2003;Simonin et al, 2008).…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 99%
“…The Hg accumulation in marine fish primarily depends on some important biokinetic parameters: assimilation from the ingested prey, uptake constants from the aqueous phase, de-toxification rate (Wang, 2012;Wang et al, 1997Wang et al, , 1998Wang and Fisher, 1999;Dang and Wang, 2011) and environmental features (e.g., Hg concentration and speciation in seawater, dietary sources, etc.) (Wang and Wong, 2003 Several studies have demonstrated that Hg concentrations in the muscles of marine organisms proportionally increase with size and age (Lange et al, 1994;Burger et al, 2001;Green and Knutzen, 2003;Simonin et al, 2008).…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 99%
“…Experimental studies on the routes of methylmercury exposure in fishes are indeed rather controversial (Honda et al 1978, Phillips & Buhler 1978, Fujiki 1980, Hall et al 1997. Kinetic modeling now offers a powerful approach for delineating the exposure of different metal species and pathways (Wang et al 1997, 1998, Wang & Fisher 1999. Within the framework of the kinetic model, however, some important parameters need to be quantified, including the assimilation efficiency from the ingested prey, the uptake-rate constant from the aqueous phase, and the elimination-rate constant, as well as some physiological and geochemical parameters such as the feeding rate of the animals and the concentrations of metals in the water and in the dietary sources.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Cr(VI) has obtained much attention because of its toxicity and mobility (Oshida et al, 1981;Holdway, 1988;Nieboer and Jusys, 1988;Wang et al, 1997;Sivakumar and Subbhuraam, 2005). Numerous reductants can reduce Cr(VI) to Cr(III).…”
Section: Introductionmentioning
confidence: 99%